Perkembangan Sosial Emosional Anak Usia Dini di Pondok Pesantren Tahfidz Hidayatul Muta'allimin - Khoiruddin, M Arif; Alwy, Susiati (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2020)
Parent plays an important role in children social and emotional development. Most of the parents lay the students education and taking care of the Islamic boarding school from an early age. Children who live in the boarding have a demanding schedule from memorizing, studying and Islamic practices continually in a long period. This could lead the children to a psychological problem. This research is aimed to know the psychology condition of the children who lived in a boarding house since early age troubled in social and emotional development. The research design and approach is descriptive qualitative. The research setting is Hidayatul Muta'alimin Islamic boarding School Gurah Kabupaten Kediri. Most of the students are children and the advanced program is tahfidz Al-Qur'an. The data sampling is the interview, observation, and some school documents. The research finding shows that no serious psychological problem for children. The social-emotional development of the children is also fine. It is caused by a friendly environment for the children and a free hand of playing on the spare time makes them away from feeling lonely, bored and they are also cheerful although live away from their parents. Moreover, the school management gives an example of how to interact socially to the students in the boarding school.